2020
DOI: 10.3390/agriculture10020033
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Activity of Sprouts from Seeds of Citrus Species

Abstract: Seeds from Citrus species represent a relevant by-product of the juice industry and a potential source of bioactive compounds such as phenols and other antioxidants. Sprouting could be an intriguing idea to enhance the content of these compounds, as explored for other fruittree species. In this experiment, the sprouting performance, the concentration of total phenols and phenolic acids, and the antioxidant activity of seeds and sprouts were evaluated for bitter orange (Citrus aurantium L. seedlings), blonde or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…In the present study, the TPCs were found as 343.70 mg GAE/100 g and 332.28 mg GAE/100 g in OSE and LSE, respectively. The TPC of CSE determined in this study was higher than those reported by previous studies (Aishwarya Reddy et al., 2018; Anagnostopoulou et al., 2006; Falcinelli et al., 2020). Anagnostopoulou et al.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…In the present study, the TPCs were found as 343.70 mg GAE/100 g and 332.28 mg GAE/100 g in OSE and LSE, respectively. The TPC of CSE determined in this study was higher than those reported by previous studies (Aishwarya Reddy et al., 2018; Anagnostopoulou et al., 2006; Falcinelli et al., 2020). Anagnostopoulou et al.…”
Section: Resultscontrasting
confidence: 73%
“…(2006) notified that the TPC of orange peel extract ranged between 3.0 and 105 mg GA/g dry extract while Falcinelli et al. (2020) found the TPC of lemon and bitter orange seeds extract ranged between 1.2 and 2.5 mg GAE/g dry weight. The TPC of citrus species depends on several factors such as the origin of species, extraction temperature and time, extraction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acids included gallic acid, vanillic acid, syringic acid, rosmarinic acid, p-coumaric acid, and trans-2-hydroxycinnamic acid. A more recent study investigating the concentration of phenolic compounds present in different Citrus seeds corroborates these findings [22]. Phenolic acids found in bitter orange seeds belong to the hydroxybenzoic acids (vanillic acid, 3.3 µg/g DW) and hydroxycinnamic acids (caffeic acid, 5 µg/g DW; trans-ferulic acid, 3 µg/g DW; and p-coumaric acid, 15 µg/g DW) families [22].…”
Section: Aurantium Seedsmentioning
confidence: 68%
“…Bitter orange, blonde orange, sweet orange, lemon, and mandarin seed ultrasound methanol extracts (Table 3) were investigated for their antioxidant ability but no differences were found in the radical scavenging activity (Falcinelli et al, 2020). Conversely, Costanzo et al (2020) demonstrated that powered Citrus reticulata seed extract tissue showed the highest antioxidant capacity (55.6 mmol TE/mg FW) compared to Citrus japonica seed extract tissue (3.2 mmol TE/mg FW).…”
Section: Antioxidant Potentialmentioning
confidence: 99%